Modern Health Worries, Somatosensory Amplification, Health Anxiety and Well-Being: A Cross-Sectional Study - Köteles, Ferenc; Simor, Péter (European Journal of Mental Health, 2014)
The study aims to investigate the relationship among modern health worries (MHWs), somatosensory amplification (SSA), health anxiety, and well-being. Questionnaires (Modern Health Worries Scale, Somatosensory Amplification Scale, Short Health Anxiety Inventory, Positive and Negative Affect Schedule, and WHO-Five Well-being Scale) were completed by 180 patients (mean age = 48.2 ± 15.76 yrs) visiting their general practitioners and by 344 undergraduate students (21.5 ± 2.09 yrs) in a cross-sectional study. According to the results, SSA and health anxiety were independently related to MHWs. Health anxiety was negatively related to indicators of general well-being. MHWs were not associated with well-being and were weakly positively connected to positive affect in the correlation analysis, while positive associations with both constructs were found after controlling for socio-economic variables, negative affect, and health anxiety in the regression analysis. MHWs are usually treated as maladaptive cognitive structures, but in the light of the present results this viewpoint might need reconsideration.